A comparative study on the antimicrobial activity and the presence of phytochemicals in the petioles and callus of J. curcas. - Gawri, Shobha; Upadhyay, Arunima (Journal of Phytology, 2012)
In the recent years J. curcas have gained lot of importance due to property to produce biodiesel. Another reason because of which this plant has gained importance is due to its medicinal properties. The latex of J. curcas has anticancer properties due to the presence of alkaloid ‘Jatrophine`. The juice of leaf is used to treat piles and bark yields a blue dye for coloring cloths. The latex, leaf, bark, and fruits contain several glycosides, tannins, phytosterols, flavonoids and steroidal sapogenins that exhibit wide ranging medicinal properties. Commercial exploration for biopharmaceuticals, antimicrobial activity and bioenergy production are some of the prospective future potential of this plant. But the question arises, whether the concentration of these secondary metabolites and antimicrobial activity is same in the fresh sample as well as tissue cultured callus. To test the same, present study was planned. For this the petioles of fresh leaves if J. curcas were cultured in the tissue normal tissue culture MS media. The callus so obtained was used for further photochemical screening and antimicrobial activity testing. The results indicate that secondary metabolites like alkaloids, glycosides, flovonoids, tannins, and phlobatannis were present in the fresh samples as well as the cultured callus but the concentration of alkaloids and glycosides were higher in the callus. Both showed antimicrobial activity. By this study we conclude that increased production of secondary metabolites can be obtained by tissue culture technique.